A case of fatal intoxication with the novel synthetic opioid N-pyrrolidino protonitazene - Wrbas, Sophia; Sundermann, Tom R.; Auwärter, Volker; Huppertz, Laura M. (International journal of legal medicine, 2025)
The presence of 2-benzylbenzimidazole-derived opioids (nitazenes) in the drug market is steadily increasing. These often highly potent synthetic opioids can cause severe, potentially fatal effects. This case report presents a fatal intoxication following the vaping of the novel synthetic opioid N-pyrrolidino protonitazene (protonitazepyne), detected in serum obtained 10 h postmortem and in multiple specimens collected at autopsy three days after death.